The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijerph17165797
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Life with HIV as an Older Adult in South African Communities: A Phenomenological Study

Abstract: The study explored how older adults experience an HIV diagnosis, deal with issues of stigma and disclosure, and navigate the healthcare system. Descriptive phenomenology was used to collect data from 20 older adults receiving antiretroviral treatment in health facilities in Gauteng Province, South Africa. Data analysis was inductive and followed the thematic approach. After diagnosis with HIV, the older adults experienced shock and disbelief, internalized their new reality of being HIV-positive, and found it d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 38 publications
4
24
0
1
Order By: Relevance
“…The stigma experienced by adults with HIV had a negative effect on post-traumatic growth [37]. Similar to what was shown in the present study, adults with HIV experienced stigma, which affected their patterns of disclosure and eventually prevented them from disclosing their trauma experience (HIV-related challenges) [36]. However, self-disclosure is a vital factor in coping because it is the first strategy for managing stress from a trauma experience and the psychological preparation for post-traumatic growth [38].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The stigma experienced by adults with HIV had a negative effect on post-traumatic growth [37]. Similar to what was shown in the present study, adults with HIV experienced stigma, which affected their patterns of disclosure and eventually prevented them from disclosing their trauma experience (HIV-related challenges) [36]. However, self-disclosure is a vital factor in coping because it is the first strategy for managing stress from a trauma experience and the psychological preparation for post-traumatic growth [38].…”
Section: Discussionsupporting
confidence: 82%
“…No study has reported on the effect of stigma experienced by nurses who cared for COVID-19 patients on post-traumatic growth, but findings from previous research about stigma and post-traumatic growth of adults with HIV [36,37] are noteworthy. The stigma experienced by adults with HIV had a negative effect on post-traumatic growth [37].…”
Section: Discussionmentioning
confidence: 96%
“…The participants in this study did not disclose to family members who would pose the highest risk of negative emotional consequences. As a disclosure approach, selective disclosure is used, particularly by older people, to protect their status and guard against stigma [43]. We observed more disclosure to siblings and parents than to sexual partners.…”
Section: Discussionmentioning
confidence: 74%
“…People present late for HIV testing because of a poor uptake of HIV testing services, fear of a positive result, and a fear of stigma [26,33,41,42]. Among older persons, HIV testing is delayed due to low self-perceptions of the risk of HIV transmission and acquisition [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation